Eksperimen Pembelajaran Matematika Dengan Strategi Teams Games Tournaments Dan Group Investigation Ditinjau Dari Gaya Belajar Siswa Kelas VII Semester Genap SMP Negeri 2 Banyudono Tahun Pelajaran 2016/2017 - Kusumaningrum, Yunita Dian, Rita Pramujiyanti Khotimah, S.Si, M.Sc (2017)
The research aims to analyze and examine: (1) The influence of learning strategies of Teams Games Tournaments and Group Investigation toward mathematics learning outcomes, (2) The influence of learning style of student toward mathematics learning outcomes, (3) The effect of the interaction between learning strategies and learning style of student towards mathematics learning outcomes. The type of this research is quantitative with quasi experimental design. The population in this research is all students of VII SMP N 2 Banyudono on academic year 2016/2017. Sampe of this research consisted of two classes, they are experiment class and control class with the sampling technique that are use is cluster random sampling. Methods of data colletion used tests, questionnaires, and documentation. Techniques od analyzed used analysis of variance two paths with different cell with a significance level of 5%. Results of the data analysis was obtained: (1) There is the influence of learning strategies of Teams Games Tournaments and Group Investigation toward mathematics learning outcomes, (2) There is the influence of learning style of student toward mathematics learning outcomes, (3) There is no interaction between learning strategies and learning style of student towards mathematics learning outcomes. Teams Games Tournaments, Group Investigation, learning style of students, mathematics learning outcomes.